Kajian Etnobotani Tradisi Ruwah Rosul : Praktik Ritual Masyarakat Kediri Sebelum Upacara Adat Pernikahan - Ratna Afieh Indraswari; Anisa Putri Sholehah; Roisah Maulidatunnisa Al Istiqomah; Derryl Jevani Achmad; Fahrul Ghani Muhaimin; Karin Anindita Widya Pitaloka; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to document and preserve the local knowledge of the people of Duwet Village, Kediri Regency, regarding the use of plants in the Ruwah Rosul tradition, which is carried out before traditional wedding ceremonies. This study uses a qualitative descriptive method with the determination of key informants (traditional leaders) through purposive sampling, followed by snowball sampling of additional informants (people who practice the tradition). Data collection was carried out through interviews, observations, and documentation, which were then validated using triangulation techniques. The data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study found 10 types of plants dominated by shrubs, with flowers being the most widely used part of the plant in each ritual arrangement. Each plant has a philosophical meaning that represents the values of prayer, hope, and harmony in life. Most species have not been evaluated for their conservation status (Not Evaluated), but conservation practices have been carried out by the community through cultivation in their yards. This study provides a new contribution by integrating aspects of ethnobotany, cultural symbolism, and local conservation into a single framework for analyzing the Ruwah Rosul tradition.